Pengaruh Tingkat Partisipasi Angkatan Kerja, Indeks Pembangunan Manusia, dan Upah Minimum terhadap Pengangguran di Banten - Rahmawati, Yolla; Izzati, Rafiqah Nur; Luthfiyyah, Faisma Nuril (Jurnal Ekonomika : INDEPENDEN, 2024)
The Unemployment is one of the issues for countries with large populations like Indonesia. This study aims to examine the influence of the Labor Force Participation Rate (LFPR), Human Development Index (HDI), and Regional Minimum Wage (RMW) on the Open Unemployment Rate (OUR) in 8 regencies/cities in Banten Province from 2019-2023. The research employs multiple linear regression analysis with panel data. The result indicate that all three variables have a simultaneous effect on the Open Unemployment Rate (OUR). Additionally, Labor Force Participation Rate (LFPR) does not have an effect on the Open Unemployment Rate (OUR). In contrast, the Human Development Index (HDI) has a significant negative effect on the Open Unemployment Rate (OUR). Meanwhile, the Regional Minimum Wage (RMW) has a significant positive effect on the Open Unemployment Rate (OUR).